Deep historical ecology: the Kula ring as a representative moral system from the Indo-Pacific. Issue 4 (7th August 2016) - Damon, Frederick H.
ABSTRACT: The timescape for this paper is human action across the changes configured through the Holocene. The landscapes it outlines contrast social action coming out of Western Europe with the very different management plans witnessed from India and China to Australia. This opening funnels into a focused view of the Kula Ring in Papua New Guinea understood as a particular realization of the Austronesian spread out of East Asia. Unlike in the Euro-American model, where an external 'nature' is constantly imported into an ever-expanding 'culture', the practices featured here show how the means of life are generated within the limits of an intensively known and made moral world. This comparative insight suggests new ways for comprehending human action on the earth.